Legalization of Village-Owned Enterprises to Improve the Community Economy in Central Maluku Regency - Sherlock Halmes Lekipiouw; Hendrik Salmon; Michael Rolando Singkery; Natanel Lainsamputty (Kosmik Hukum, 2024)
Law Number 6 of 2014 concerning Villages has become a comprehensive regulation regarding villages. In contrast to Law Number 32 of 2004, the regulation on BUMDe in the new Village Law is more comprehensive. BUMDes is still positioned as a village economic organization that has an important role in achieving the welfare of the community, villages, and village governments. The purpose of this study is to study and analyze the Legalization of Village-Owned Enterprises as a Means of Improving the People's Economy in Central Maluku Regency and to study and analyze the Legalization of Village-Owned Enterprises Can Improve the People's Economy in Central Maluku Regency. The research method is sociolegal with a regulatory approach and observation as well as interviews with the Tananahu government and the Central Maluku Government. The results of the research show that Tananahu's Owned Enterprises have not yet had legality through village regulations, even though their businesses have been petrified in increasing village income. So it is necessary to legalize Tananahu -owned Enterprises and also in villages in Central Maluku Regency.